Engineered Microorganisms for Production of Biocommodities - Rautela A.; Kumar S. (My University, 2025)
Biocommodity engineering deals with the engineering of organisms to produce biocommodities such as energy fuels, polymers, therapeutic proteins and peptides, and hormones. It is different from biotechnology in the aspects of economics, scale up, and cost of production. Being different also biocommodity engineering cannot be separated from biotechnology. Molecular biology forms the basis of biocommodity engineering, and recent advances in the genetic toolboxes and genome sequences of the organisms lead to its development. Earlier plants were the primary source of secondary metabolites which are now being produced microbially through genetic modification of microorganisms. Biocommodities produced are biodegradable in nature from sustainable sources. The chapter gives the basic principles of genetic engineering to give insight about how the organism can be modified using enzymes and different techniques for the production of biopolymers, organic acids, therapeutic proteins, and photosynthetic production of biofuels. Each section deals with the problems during conventional production of these biocommodities and development in the genetically engineered organism. © 2022 John Wiley & Sons, Inc.